(untitled) (Zoological Records and Reviews, 2023)
Pollinators – primarily bees, butterflies, hoverflies, and moths – provide essential ecosystem services for both wild plant reproduction and agricultural crop production, with an estimated one-third of global food production dependent on animal pollination. In South Asian agricultural systems, where a diverse array of insect-pollinated crops including sunflower, mustard, cotton, pulses, and various horticultural crops are cultivated, the diversity and abundance of pollinator communities are critical determinants of yield and quality. This study presents a comprehensive assessment of pollinator diversity and abundance across seven crop systems in Andhra Pradesh and Karnataka, India, using standardised transect walks, pan trap arrays, and malaise trapping at 56 crop fields over two flowering seasons (2021-2022). A total of 284 pollinator species from 8 orders and 42 families were documented, dominated by Apoidea (128 species), Lepidoptera (84 species), and Syrphidae (48 species). Pollinator species richness and visit frequency varied significantly among crop types, with sunflower supporting the highest total pollinator diversity (mean 84.4 species per field). Landscape semi-natural habitat proportion, field margin floral diversity, and pesticide application frequency are the three strongest predictors of pollinator richness. Experimental exclusion of pollinators confirmed yield reduction of 18.4-42.4% across insect-pollinated crops. The results confirm the high economic value of pollination services and identify management interventions to enhance pollinator diversity in South Asian crop landscapes.